Evaluation the effect of gibberellic acid, carbon disulfide and thiourea on breaking the dormancy and germination of potato minitubers - shabnam hasrak; Abdolreza Bagheri; Reza Zarghami (علوم و فناوری بذر ایران)
Reducing the minituber dormancy has economic importance . The current study was aimed to find the best dormancy breaking treatment to reduce minituber dormancy of two commercial varieties (Sante and Agria). Since minituber dormancy period depends on different factors, the individual effects of treatments i.e. GA3 (0.05 and 0.07gl-1), thiourea (10 and 20gl-1) and CS2 (25 and 50mlm-3), genotype background (different dormancy periods), and minituber size (1.5, 2.5 and 3.5cm), were evaluated on minituber dormancy period. In addition to dormancy period, the effect of mentioned factors were investigated on sprout numbers and sprout length. Results showed that although CS2 and thiourea had good effects on the reduction of minituber dormancy, the detailed consideration of derived sprouts showed that it cannot be introduced as an appropriate dormancy breaking treatment. According to the results, GA3 (0.05gl-1) was found to be the best treatment for reducing dormancy period in both cultivars. GA3 (0.05gl-1), in addition to break the dormancy of different minituber sizes of both cultivars, had good effect on sprouting related parameters of treated minitubers.